2023
DOI: 10.3390/app13116660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drying–Wetting Cycle and Fines Content on Hysteresis and Dynamic Properties of Granite Residual Soil under Cyclic Loading

Abstract: In southern China, granite residual soil (GRS) is widely used as road base material. Thus, it is important to study the effects of hot and rainy climates and cyclic loads generated by trains on the dynamic properties of GRS. In this work, by means of dynamic triaxial tests, the effects of the number of drying and wetting (D–W) cycles, fines content and number of load cycles on the hysteresis curve, dynamic shear modulus Gd and damping ratio λ of GRS are systematically investigated. The experimental results ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The soil specimen was prepared by the compaction method in a mold with 39.1 mm in diameter and 80 mm in height. After compaction, the mold was removed and the specimen was sealed in cling film [41][42][43]. In order to study the influence of moisture content and stress level on the permanent deformation characteristics of Yellow River alluvial silt, silt specimens with three moisture contents were prepared in this paper.…”
Section: Test Materials and Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The soil specimen was prepared by the compaction method in a mold with 39.1 mm in diameter and 80 mm in height. After compaction, the mold was removed and the specimen was sealed in cling film [41][42][43]. In order to study the influence of moisture content and stress level on the permanent deformation characteristics of Yellow River alluvial silt, silt specimens with three moisture contents were prepared in this paper.…”
Section: Test Materials and Specimen Preparationmentioning
confidence: 99%
“…The soil specimen was prepared by the compaction method in a mold with 39.1 mm in diameter and 80 mm in height. After compaction, the mold was removed and the specimen was sealed in cling film [41][42][43].…”
Section: Test Materials and Specimen Preparationmentioning
confidence: 99%
“…Numerous studies have examined the degradation of the engineering properties of GRS caused by drying-wetting (DW) cycles. The impact of DW cycles on the macroscopic mechanical behavior of GRS has been investigated [10][11][12]. For instance, Jian et al [13] found that the cohesion of GRS decreased significantly during the early stages of DW cycles, then gradually stabilized over time, while the internal friction angle did not exhibit a clear change.…”
Section: Introductionmentioning
confidence: 99%